Effects of exogenous Ca 2+ on photosynthetic characteristics and fruit quality of pepper under waterlogging stress - Ou,Li-Jun (Instituto de Investigaciones Agropecuarias, INIA, 2017)
ABSTRACT Pepper is one of the most important vegetable crops in China. Consumers in China are increasingly demanding high quality pepper (Capsicum annuum L.) fruit. As in flood crops, natural disasters, such as flooding, might not only affect pepper yield, but also significantly impact fruit quality. Thus, it is necessary to study the change in fruit quality under waterlogging stress and seek an improved method. Pepper '5901' was the experimental material; we investigated the effects of spraying exogenous Ca2+ on the photosynthetic characteristics and quality of pepper plants under waterlogging stress. We found that waterlogging significantly reduced the photosynthesis rate (PN), stomatal conductance (g s), fruit length, individual fruit diameter, individual fruit fresh weight, and soluble protein, soluble sugar, free amino acid, P, Fe, vitamin C (Vc), and vitamin E (Ve) contents. It significantly decreased the expression levels of 1-aminocyclopropane-1-carboxylate oxidase 1 (ACO-1), catalase (CAT-2), and pyruvate kinase (PK) genes, and it significantly increased intracellular CO2 concentration, capsaicin content, and the expression level of the alcohol dehydrogenase-1 (ADH-1) gene. The parenchymatous cells in the root system and stem were loosely arranged, the degree of lignification was deepened, leaves became thinner, and palisade tissue thickness was reduced. Exogenous Ca2+ significantly enhanced capsaicin content, alleviated the extent of the reduction in the abovementioned physiological parameters, and maintained epithelial cell shape in the mesophyll layer. It maintained the intactness of the cell wall in the root system, cell membrane, and pulp cavity; it also reduced cell injury and stimulated the expression levels of ACO-1, ADH-1, CAT-2, and PK genes. Compared to the normal control, expression levels of these genes increased by 52.03%, 99.48%, 40.78%, and 125.67%, respectively. The present study indicates that spraying exogenous Ca2+ can effectively alleviate injury to pepper plants caused by waterlogging stress and improve the quality of pepper fruit.